2003
DOI: 10.1038/nature01665
|View full text |Cite
|
Sign up to set email alerts
|

Universal alignment of hydrogen levels in semiconductors, insulators and solutions

Abstract: Hydrogen strongly affects the electronic and structural properties of many materials. It can bind to defects or to other impurities, often eliminating their electrical activity: this effect of defect passivation is crucial to the performance of many photovoltaic and electronic devices. A fuller understanding of hydrogen in solids is required to support development of improved hydrogen-storage systems, proton-exchange membranes for fuel cells, and high-permittivity dielectrics for integrated circuits. In chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

70
848
8
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,164 publications
(928 citation statements)
references
References 21 publications
70
848
8
2
Order By: Relevance
“…21 The refined lattice constants were consistent for samples deposited over a range of pH values (5.5-7.5) and deposition potentials (-1.3 V to -0.85 V), consistent with previous results from our group over a more acidic pH range (4-5.5). 5 Qualitative comparisons of relative peak heights ( Figure 1) also confirmed that, while our samples are polycrystalline, there is a preferred (002) orientation in the deposit, which is typical for electrodeposited ZnO. 4,15,22 This (002) texture is moderately accentuated for samples deposited at -1.1 V (pH 6.5), coinciding with a morphological change from hexagonal crystallites to rice-like structures, as shown in Figure 2, and reported previously.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…21 The refined lattice constants were consistent for samples deposited over a range of pH values (5.5-7.5) and deposition potentials (-1.3 V to -0.85 V), consistent with previous results from our group over a more acidic pH range (4-5.5). 5 Qualitative comparisons of relative peak heights ( Figure 1) also confirmed that, while our samples are polycrystalline, there is a preferred (002) orientation in the deposit, which is typical for electrodeposited ZnO. 4,15,22 This (002) texture is moderately accentuated for samples deposited at -1.1 V (pH 6.5), coinciding with a morphological change from hexagonal crystallites to rice-like structures, as shown in Figure 2, and reported previously.…”
Section: Resultssupporting
confidence: 88%
“…This may be due to variations in the electrodeposit coverage (parameter f in Eq. 4), since earlier studies 5 have shown that small pinholes can occur in our electrodeposits. Fabregat-Santiago et al have also shown that sample-dependent capacitance can occur when there are sample/electrolyte interactions.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…In the majority of cases, H 0 i is never the most stable charge state at any Fermi level (E F ). This is referred to as H i exhibiting "negative-U " character [2]. The position of the (+/−) transition level shows universal behavior across many different materials, when aligned on an absolute energy scale, and can serve as a reference for estimating band alignments [2].…”
Section: Introductionmentioning
confidence: 99%